Institutionalising integrity in the Nigerian public service (2003)
Studies on corruption and ethics in Nigeria were initially dominated by a theory of cultural determinism. A new orthodoxy underlined by neo-Iiberal ideas regarding the role of the state in resource allocation has gradually become dominant since the 1990s. But the latter feeds on the basic premises of cultural determinism. Rejecting both perspectives, this paper argues that corruption as a universal phenomenon, straddling both public and private sector organisations, is better addressed from the view point of the competing sources of ethical decision making for individuals in the public service. This provides direction for a realistic ethics programme towards institutionalizing integrity in the Nigerian public service.